Managing rebound pain after regional anesthesia - Felipe Muñoz-Leyva; Javier Cubillos; Ki Jinn Chin (Korean Journal of Anesthesiology, 2020)
Rebound pain after regional anesthesia can be defined as transient acute postoperative pain that ensues following resolution of sensory blockade, and is clinically significant, either with regard to the intensity of pain or the impact on psychological well-being, quality of recovery, and activities of daily living. Current evidence suggests that it represents an unmasking of the expected nociceptive response in the absence of adequate systemic analgesia, rather than an exaggerated hyperalgesic phenomenon induced by local anesthetic neural blockade. In the majority of patients, it does not appear to significantly impact cumulative postoperative opioid consumption, quality of recovery, or patient satisfaction, and is not associated with longer-term sequelae such as persistent post-surgical pain. Nevertheless, it must be considered whenever regional anesthesia is incorporated into perioperative management. Strategies to mitigate the impact of rebound pain include routine prescribing of a systemic multimodal analgesic regimen, as well as patient education on appropriate expectations regarding block offset and expected surgical pain, and timely initiation of analgesic medication. Prolonging the duration of action of regional anesthesia with continuous catheter techniques or local anesthetic adjuncts may also help alleviate rebound pain, although further research is required to confirm this.